Lecturer’s Attitude towards Advance Technology and Its Impact to the Learning Process: Case study in Tangerang City Campuses - Harisa Mardiana (Journal of Educational Science and Technology (EST), 2018)
This research aimed to determine the qualifications of lecturers in the field of social science depended on the use of advance technology, especially the power points, the Internet, and social media site. The problem that some of the lecturers preferred to use the traditional way of teaching, such as whiteboard and marker, lectures. This study research was to observe the categories of lecturers’ knowledge, ages and gender in using technology in the classroom. Also we sought lecturers’ difficulty in using technology to conduct the teaching and learning process in the classroom. The research design in this study was a quantitative method, with giving questionnaires to 107 lecturers in Tangerang City campuses. Data collection technique was taken by conducting observation, questionnaires and interview and data analysis. The result of this study research showed that there are 5 categories of lecturers’ attitudes towards advance technology based on their knowledge, ages and gender. And the purpose of the study research is to give an opportunity to increase lecturers’ qualifications for 2st century learning process and to leverage advance technology in campuses which it is to deliver contents and to engage students and lecturers learning process in ways not previously possible.